A Study of the Creep-Fatigue Damage Mechanism of a P92 Welded Joint Using Nanoindentation Characterization - Zhangmin Jin; Zhihui Cai; Xuecheng Gu; Zhiqiang Wang; Yiwen Han; Ting Yu; Yuxuan Song; Zengliang Gao; Zhongrui Zheng (Metals)
In fossil fuel and nuclear power plants, welded joints continuously experience creep-fatigue loading, which can result in premature cracking during the in-service term. To study the creep-fatigue interactive (CFI) behavior, the CFI test of P92 steel was performed with different strain rates at 823 K. Results indicate that the short cycle life is measured with the increasing strain rate. Relying on the scanning electron microscope, the fracture mechanism of P92 steel gradually changes from fatigue-dominating to creep-fatigue interactive damage with the increasing strain rate. The hardness (H), elastic modulus (E) and creep deformation were then measured by nanoindentation, and the strain rate sensitivity (m) was estimated. The relation between the degenerated mechanical properties and microstructural evaluations, i.e., enhanced grain size and nucleation of creep voids, was established, and the damage mechanism was discussed.